The effect of corporate governance on the relationship between corporate social responsibility disclosure and corporate value - Herlina Samsi (Universitas Hayam Wuruk Perbanas, 2014)
This study aims to reveal the effect of corporate governance on the relationship between corporate social responsibility disclosure and corporate value. The data were taken from sustainability reports, annual reports, and financial statements of companies listed in Indonesia Stock Exchange from sector one to seven in a row during 2009-2010. This study replicates the research by Rustiarini (2010). It shows that corporate social responsibility and corporate governance disclosure, both simultaneously and partially, have significant effect on corporate value. Corporate governance as a moderating variable does not affect the relationship between corporate social responsibility disclosure and corporate value. Of 28.9 percent of variation in corporate value is explained by variables of corporate social responsibility disclosure, corporate governance, and interaction variables used in the model, while the rest of 71.1 percent must be caused by other variables. For further studies, the researchers could take longer period with other variables (i.e. variables of corporate governance, return on assets, cash holdings, dividend payout ratio, and investment opportunity) and use another index (i.e. corporate governance index issued by the Indonesian Institute for Corporate Governance (IICG).